2018
DOI: 10.5010/jpb.2018.45.1.036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan and chitosan-nanoparticles on post harvest quality of banana fruits

Abstract: In this study, we evaluated the effect of different concentrations of chitosan and chitosan nanoparticles as edible coating in extending shelf life and maintaining the quality of banana fruits (Musa acuminata AAA group). The fruit treated with 1.15% chitosan, 1.25% chitosan and chitosan nanoparticles then store at ambient temperature (25±1°C). The shelf-life of banana, starch content, weight loss, pulp to peel ratio, total soluble solid, surface morpholgy of banana peel and sensory evaluation were analysed. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
96
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(116 citation statements)
references
References 28 publications
19
96
0
1
Order By: Relevance
“…The peaks around 3400 cm −1 at FTIR results are related to the stretching vibration of the –NH 2 (chitosan samples) or –OH groups (alginate and xanthan samples) [ 21 , 22 , 23 ]. The high intensity of vibration in this region for G, C1G2, and C1A2 samples indicates that the hydrogen bonding is enhanced, since this peak is also related to the intramolecular hydrogen bonds present in the structure of all three polymers and polyelectrolytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks around 3400 cm −1 at FTIR results are related to the stretching vibration of the –NH 2 (chitosan samples) or –OH groups (alginate and xanthan samples) [ 21 , 22 , 23 ]. The high intensity of vibration in this region for G, C1G2, and C1A2 samples indicates that the hydrogen bonding is enhanced, since this peak is also related to the intramolecular hydrogen bonds present in the structure of all three polymers and polyelectrolytes.…”
Section: Discussionmentioning
confidence: 99%
“…At pH 7.0 (after the neutralization step of the “onion-like” process), the proportion of protonated and unprotonated amino groups from chitosan could have produced changes in the intensity of this peak. The hypsochromic shift of the C=O peak pointed to the interaction between NH 3 + groups of chitosan and negative groups of xanthan or alginate [ 21 ]. In a similar study, Takara et al showed that treatment of NaOH decreased the intensity of amino group peaks (around 1650 cm −1 ) in chitosan films due to deprotonation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Musa acuminata AAA group CHT nanoparticles Shelf life extension and maintenance of fruit quality [41] Vaccinium myrtillus CHT + procyanidins Promotion of quality maintenance and inhibition of fruit pathogens growth [42] Citrus reticulata Blanco CHT + Ficus hirta Vahl. fruits extract…”
Section: Plant Species Cht-based Polymer Effect Referencementioning
confidence: 99%
“…CHT + photoactivated chlorophyllin Extension of fruit shelf life and inhibition of pathogens growth [44] Zizyphus jujuba Mill. cv Dongzao CHT/nano-silica/sodium alginate Extension of fruit shelf life and inhibition of pathogens growth [45] Ginkgo biloba L. CHT/nano-TiO 2 and CHT/nano-SiO 2 Preservation of seeds quality [46] Application of CHTNP extended shelf life and maintained quality of banana fruits [41], while CHT + procyanidins coating promoted quality maintenance and inhibited microbial growth of fresh blueberry [42]. Coating with Ficus hirta Vahl.…”
Section: Plant Species Cht-based Polymer Effect Referencementioning
confidence: 99%
“…The use of these biodegradable materials could to some extent help solve the waste problem [9]. Our previous study showed that chitosan as edible coating for banana fruit could slow down ripening of the banana [10,11].…”
Section: Introductionmentioning
confidence: 99%